Comparison of Classical Cytogenetics Versus Interphase FISH in Diagnosis of Mosaic Form of Turner Syndrome - Shohreh Shargh; Simin Tagavi; Seyed Mojtaba Mohaddes (Medical Journal of The Islamic Republic of Iran, 2010)
Background:Mosaic form of turner syndrome that represented by two or more  cell lines in an affected individual, often has limitation for detection with classical  cytogenetic methods. The present study was carried out to compare the efficiency of  interphase Fluorescence In Situ Hybridisation (FISH) and cytogenetic techniques in  detection of mosaic form of turner syndrome.  Methods: All candidate samples for turner syndrome were surveyed with both interphase FISH using DXZ1 as a chromosome X specific probe and the GTG- banding methods. The chi square test was used and a P-value of less than 0.05 was considered as being significant.  Results: Asignificant difference was observed between results obtained from the  application of the two methods under study (P<0.05), indicating that the interphase  FISH is favourably compares to conventional cytogenetics in detection of mosaic  form of X chromosome aneuploidy, as an extended number of cells can be scored in a  limited time.  Conclusion: The results indicate that using the two techniques in parallel allow accurate differentiation between mosaicism and homogenous aneuploidy of X chromosome, and thus both numerical and structural aberrations of the X will be analyzed.